(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
A survey of bael genotypes was conducted in the districts of Ajmer, Churu, Jaipur, and Jhunjhunu in Rajasthan during 2021-22 and 2022-23.The collected genotypes exhibited significant variability in fruit morphology and physico-chemical characteristics. The number of fruits per tree ranged from 65 to 145, with fruit yield per tree varying between 22.79 kg and 176.6 kg. Fruit weight ranged from 0.33 kg to 2.85 kg across the genotypes. The important fruit traits, such as fruit length, ranged from 9.05 cm to 18.45 cm, shell weight per fruit varied from 115.25 g to 374.74 g, shell thickness ranged from 0.16 cm to 0.32 cm, and seed weight per fruit from 0.15 g to 0.32 g. The total soluble solids (TSS) ranged from 29.15 to 39.46 °Brix among the genotypes analyzed. Based on the overall assessment, the genotypes SKN-15 and SKN-2 were identified as the most promising.